Membina Keterampilan Abad 21: Efektivitas RICOSRE dan Flipbook Digital dalam Meningkatkan Kolaborasi Siswa - Ramdani, Dani; Idaman, Raina Putri; Ali, Mufti (Universitas Negeri Jakarta, 2025)
This study is expected to provide an overview of the utilization of the RICOSRE learning model assisted by the digital flipbook media to collaborative skills of 11th-grade students on the human excretory system topic. Collaborative skills are critical in biology because they enable students to work together, discuss, and get an in-depth understanding of the concept, thus promoting learners' efficiency and readiness for scientific problems. The study applied a quasi-experimental design to a non-equivalent pretest-posttest control group. The population comprised seven classes in 11th grade of the National Senior High School 6 Tasikmalaya science class. However, the sample was three classes, selected using purposive sampling, whereby XI Science 3 was the experimental class, XI Science 2 was a positive control class, and XI Science 5 was a negative control class. The Collaboration Self-Assessment Tool 44-item questionnaire was used to collect data and proved valid and reliable. The results of the ANCOVA test show that the learning model used in the experimental class achieved significant results compared to the model used in the control class. Moreover, the LSD test could measure the difference level; hence, workload RICOSRE with a digital flipbook was better than RICOSRE with PowerPoint and Discovery Learning with PowerPoint. The RICOSRE model supported by digital flipbooks significantly enhanced students’ collaborative skills that help in keeping students active, interactive, and cooperative in learning biology. The findings recommended that teachers and curriculum developers apply this model to create engaging lessons that will keep students in continuing collaboration.